2004
DOI: 10.4049/jimmunol.172.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression and Ig Transcription in PU.1/Spi-B-Deficient Progenitor B Cell Lines

Abstract: A number of presumptive target genes for the Ets-family transcription factor PU.1 have been identified in the B cell lineage. However, the precise function of PU.1 in B cells has not been studied because targeted null mutation of the PU.1 gene results in a block to lymphomyeloid development at an early developmental stage. In this study, we take advantage of recently developed PU.1−/−Spi-B−/− IL-7 and stromal cell-dependent progenitor B (pro-B) cell lines to analyze the function of PU.1 and Spi-B in B cell dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 69 publications
(85 reference statements)
3
58
0
Order By: Relevance
“…Similar to the phenotype of PU.1 Ϫ/Ϫ Spi-B Ϫ/Ϫ pro-B cells (29), we found that steady-state levels of sterile transcripts initiating from the IgH intronic enhancer (I ) were increased relative to WT-R1 pro-B cells (Fig. 4A).…”
Section: Increased Igh Sterile Transcripts and Reduced Fc␥riib Transcsupporting
confidence: 58%
See 4 more Smart Citations
“…Similar to the phenotype of PU.1 Ϫ/Ϫ Spi-B Ϫ/Ϫ pro-B cells (29), we found that steady-state levels of sterile transcripts initiating from the IgH intronic enhancer (I ) were increased relative to WT-R1 pro-B cells (Fig. 4A).…”
Section: Increased Igh Sterile Transcripts and Reduced Fc␥riib Transcsupporting
confidence: 58%
“…We have previously shown that PU.1 Ϫ/Ϫ Spi-B Ϫ/Ϫ pro-B cells have a phenotype similar to pre-B cells with increased CD25 and decreased c-Kit surface expression relative to wild-type (WT) pro-B cells. In addition, PU.1 Ϫ/Ϫ Spi-B Ϫ/Ϫ pro-B cells express increased IgH sterile transcripts relative to WT pro-B cells (29). The PU.1 Ϫ/Ϫ Spi-B Ϫ/Ϫ phenotype could be recapitulated by ectopic expression of a mutant form of PU.1 lacking an activation domain (29).…”
mentioning
confidence: 78%
See 3 more Smart Citations